Etika dalam Asesmen Psikologi di Bidang Bimbingan dan Konseling (International Forum of Researchers and Lecturers, 2025)
Psychological assessment plays a crucial role in guidance and counseling by providing a deeper understanding of an individual’s psychological state however, it must be conducted in accordance with professional ethical standardsto protect the rights and dignity of clients. This article explores core ethical principles in psychological asseeement-such as informed consent, confindentiality, profesional competence, and the appropriate use of valid instruments. Based on recent literature, this paper highlights thataderece to ethical assessmens the counselor-client relationship and enhances psychological intervention outcomes.